Disruption of the glucocorticoid receptor gene in the nervous system results in reduced anxiety - Tronche, François; Kellendonk, Christoph; Kretz, Oliver; Gass, Peter; Bock, Rudolf; Klein, Rüdiger; Schütz, Günther (Nature genetics, 1999)
The glucocorticoid receptor (Gr, encoded by the gene Grl1) controls transcription of target genes both directly by interaction with DNA regulatory elements and indirectly by cross-talk with other transcription factors. In response to various stimuli, including stress, glucocorticoids coordinate metabolic, endocrine, immune and nervous system responses and ensure an adequate profile of transcription. In the brain, Gr has been proposed to modulate emotional behaviour, cognitive functions and addictive states. Previously, these aspects were not studied in the absence of functional Gr because inactivation of Grl1 in mice causes lethality at birth (F.T., C.K. and G.S., unpublished data). Therefore, we generated tissue-specific mutations of this gene using the Cre/loxP -recombination system. This allowed us to generate viable adult mice with loss of Gr function in selected tissues. Loss of Gr function in the nervous system impairs hypothalamus-pituitary-adrenal (HPA)-axis regulation, resulting in increased glucocorticoid (GC) levels that lead to symptoms reminiscent of those observed in Cushing syndrome. Conditional mutagenesis of Gr in the nervous system provides genetic evidence for the importance of Gr signalling in emotional behaviour because mutant animals show an impaired behavioural response to stress and display reduced anxiety.